2015
DOI: 10.1021/acs.langmuir.5b03733
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Investigation of Nanoparticles’ Role in Mobilizing Trapped Oil Droplets in Porous Media

Abstract: The flow of multiple fluid phases in porous media often results in trapped droplets of the nonwetting phase. Recent experimental and theoretical studies have suggested that nanoparticle aqueous dispersions may be effective at mobilizing trapped droplets of nonwetting fluid (oil) in porous media. Hypotheses to explain the observation include the nanoparticles' modification of solid wettability, droplet stabilization, and changes in interfacial tension and interface rheology. However, because it is difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 59 publications
(82 reference statements)
0
26
0
Order By: Relevance
“…Our rationale for using an analogous relationship is to obtain a realistic range of retention constant values in a two-site model at disparate scales. This empirical relation, given by (9), is based on mechanisms of deposition, interception, and sedimentation [36,38,51,70]:…”
Section: Retention Model Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our rationale for using an analogous relationship is to obtain a realistic range of retention constant values in a two-site model at disparate scales. This empirical relation, given by (9), is based on mechanisms of deposition, interception, and sedimentation [36,38,51,70]:…”
Section: Retention Model Constantsmentioning
confidence: 99%
“…Even though they have been widely used in various industries such as the medical field for enhanced imaging [1,2], targeted drug-delivery, and biosensing [3][4][5], NPs have yet to be adapted for their potentially attractive application in porous media. These applications may include enhanced hydrocarbon recovery through nanosuspensions [6][7][8][9], subsurface mapping through nanosensors [10,11], hydraulic fracture characterization through nanomagnetization of reservoirs [12], hydraulic fracturing fluid with better proppant transport ability through nanofoams [13], and convective heat transfer [14,15]. Many of these applications within porous media, such as enhanced oil recovery and subsurface mapping, would require the NPs to travel the depth and breadth of the targeted reservoir zone, which typically extend to hundreds of feet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been implemented to investigate different multi-phase flow phenomena in porous media at the pore level. Due to some recent advancement in micromodel chips, such as design of single-channel patterns with variable cross-section size, it provides opportunity to study the emulsion flow in parallel conduits [7], trapping of non-wetting phase at pore-throat structures and geometries pertinent to enhanced oil recovery [8] and the research in reservoir engineering. Additionally, 2-D and 3-D features in the micromodel geometry has been developed and commonly used but both have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…while in (3-D), physics is required in porous media especially for multi-phase flow where capillary effects are prominent, resolution and material limit, and 3-D printing technology [11]. Unfortunately, these limitations make it unmanageable to construct a 3-D micromodel as a basic model of truly micron-scale permeable medium [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong reservoir heterogeneity and fluid channeling, it is reported that the normal water flooding can only produce about 30% of the total reserves of oil 3 . To overcome these difficulties, several EOR techniques have been proposed, including polymer flooding 3–5 , oil-in-water (O/W) emulsions 6,7 and foam displacement 8 . Among these techniques, polymer flooding is considered as one of the most promising technologies 9 .…”
Section: Introductionmentioning
confidence: 99%